Model Interaksi antara Kebijakan Sekolah, Iklim Sekolah, dan Pembelajaran Agama Islam dalam Konteks Ketahanan Siswa - Budiman Budiman; Juli Ahirin; Sisvi Kartika; Ahmad Syukri; Idi Warsah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to build and confirm a conceptual interaction model between school policy, school climate, and Islamic religious learning in the context of student resilience. These four variables were tested by formulating six hypotheses. This research uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to explore the interactive effects of school policies, school climate, and Islamic religious learning on student resilience. With a sample of 500 teachers and 500 students from Madrasah Aliyah Negeri in Bengkulu, this research used a validated questionnaire to measure these variables. Data were analyzed using the SmartPLS 4 application to evaluate measurement and structural models. The results of the analysis show that school policies have a positive and significant impact on student resilience with a coefficient of 0.212, a T value of 6.495, and a P value approaching 0.000; towards Islamic religious learning with a coefficient of 0.398, a T value of 14.137, and a P value approaching 0.000; and on school climate with a coefficient of 0.683, a T value of 22.063, and a P value approaching 0.000. School climate also positively and significantly impacts Islamic religious learning with a coefficient of 0.542, a T value of 19.079, and a P value of close to 0.000. It has a more minor but significant effect on student resilience with a coefficient of 0.164, a T value of 2.387, and a P value of 0.017. Islamic religious learning strongly impacts student resilience with a coefficient of 0.539, a T value of 10.580, and a P value approaching 0.000. In conclusion, these results confirm that the model built is well-structured and can be generalized. Keywords: Islamic Learning , School Policy, School Climate, Student Resilience